Impact of donor multidrug‐resistant organisms on solid organ transplant recipient outcomes. Issue 1 (10th January 2022) - Anesi, Judith A.; Blumberg, Emily A.; Han, Jennifer H.; Lee, Dong Heun; Clauss, Heather; Hasz, Richard; Molnar, Esther; Alimenti, Darcy; Motzer, Andrew R.; West, Sharon; Bilker, Warren B.; Tolomeo, Pam; et al.
Abstract: Background: The impact of donor colonization or infection with multidrug‐resistant organisms (MDROs) on solid organ transplant (SOT) recipient outcomes remains uncertain. We thus evaluated the association between donor MDROs and risk of posttransplant infection, graft failure, and mortality. Methods: A multicenter retrospective cohort study was performed. All SOT recipients with a local deceased donor were included. The cohort was divided into three exposure groups: recipients whose donors had (1) an MDRO, (2) a non‐MDRO bacterial or candidal organism, or (3) no growth on cultures. The primary outcomes were (1) bacterial or invasive candidal infection within 3 months and (2) graft failure or death within 12 months posttransplant. Mixed effect multivariable frailty models were developed to evaluate each association. Results: Of 658 total SOT recipients, 93 (14%) had a donor with an MDRO, 477 (73%) had a donor with a non‐MDRO organism, and 88 (13%) had a donor with no organisms on culture. On multivariable analyses, donor MDROs were associated with a significantly increased hazard of infection compared to those with negative donor cultures (adjust hazard ratio [aHR] 1.63, 95% CI 1.01–2.62, p  = .04) but were not associated with graft failure or death (aHR 0.45, 95% CI 0.15–1.36, p  = .16). Conclusions: MDROs on donor culture increase the risk of early posttransplant infection but do not appear to affect long‐term graft or recipient survival, suggesting organ donors with MDROs on culture may be safely utilized. Future studies aimed at reducing early posttransplant infections associated with donor MDROs are needed.